Banking Crises and Boom-Bust Dynamics: Evidence for Italy (1861-2016) - Silvana Bartoletto; Bruno Chiarini; Elisabetta Marzano; Paolo Piselli (Center for Economic Studies and ifo Institute (CESifo), 2018)
The financial crises of 2007-2008 and the subsequent worldwide recession show the importance of exploring the correlation between financial and real crises. Starting from our new estimation of the Italian business cycle (Bartoletto et al., 2017), we analyze the linkage between banking crises and the business cycle in Italy over the last two centuries. The vast literature on banking crises in Italy is dominated by the narrative approach. In this work we aim to advance the argument one step further by integrating the narrative approach with an empirical VAR analysis, distinguishing between slowdown and inner-banking crises according to the business cycle phase in which they occur. Our long-run analysis proves that not all the banking crises have a connection with real activity and that not all the crises occurring close to a GDP contraction were associated to a boom-bust mechanism.
Keywords: E32; E44; N13; N14; 330; business fluctuations; financial cycle; bank credit; banking crisis; VAR